(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Who are the people on the fringes of society and what is society’s attitude towards reducing differences? Purpose: To present key groups of people who have been recognized by society as different and what is the attitude towards them. Method: We used a descriptive method where we collected literature and information, reviewed and analyzed them. Results: The research showed that society still does not treat people who deviate from the average equally. Much of the reason is at the state level, where there are more systemic deficiencies. Organization: The research can be useful for organizations, associations that deal with specific areas of individual groups of people who have been gripped by a certain stigma, that they deviate from the normal state as recognized by the general population. Society: Based on the findings and review of the literature, society can become aware of individual deviations in people’s thinking and perception. It can serve to subvert or at least loosen certain assumptions. Originality: The research is useful for the purpose of the learning process at one of the faculties of the southeastern region. Limitations/Future Research: The research is limited to a literature review and the author’s personal thinking. The continuation of the research can be extended to surveying, involving societies from the field of research and extending it to other groups of people.